Essays on the economics of natural disasterws: evidence of the impacts of drought on socioeconomic aspects in the northeast region of Brazil - Martins, Francisco Mário Viana (2024)
The present thesis seeks to provide evidence of the impacts of drought on different socioeconomic aspects, being structured in three chapters, focusing on the Northeast Region of Brazil, an area with a high level of social and economic vulnerability to the pressures of climate change. In the first chapter, we studied how a long-lasting drought event affected the accumulation of socio-emotional skills in adolescents. Socio-emotional skills are key determinants of adult life outcomes. Significant changes in economic conditions can affect the formation of such skills, especially at more vulnerable ages. From 2012 and 2017, the Brazilian semiarid region was exposed to a long-lasting exogenous drought. Comparing students exposed and not exposed to drought, we found evidence that the drought episode significantly reduced students' conscientiousness skills, a skill related to persistence, organization and focus. We confirm these results by investigating facets associated with the socioemotional traits of conscientiousness and other related outcomes such as student aspirations. We also found a heterogeneous effect according to maternal education, moderating the impact of the drought shock on socio-emotional skills. The second chapter sheds light on the importance of local fiscal conditions to mitigate the effects of drought shocks during the gestational period on infant health outcomes, especially infant mortality. We compare municipalities exposed to drought shocks during the in utero period with those that did not experience such exposure, incorporating local fiscal conditions as a moderating factor in this analysis. The results found suggest that the fiscal capacity of municipalities is a significant factor in mitigating the effects of drought shocks on infant mortality, when we consider the indicators of fiscal autonomy and budget rigidity. We also found that municipalities with a more favorable fiscal situation tend to reduce the adverse impacts of in utero exposure to drought on infant mortality, particularly in cases of perinatal conditions. Furthermore, we found that the occurrence of drought in the first trimester of pregnancy increases infant mortality and this effect is mitigated in municipalities with greater fiscal capacity, being more pronounced in municipalities with a medium population size. Finally, the third chapter provides empirical evidence of the impact of the drought from 2012 to 2017 on the finances of municipalities in the northeastern semiarid region. We used a panel event study strategy to analyze the causal and dynamic effect of the prolonged drought on municipal government finances, comparing (before and after) the most and least exposed municipalities. The observed results show that the prolonged drought shock leads to a decrease in current expenditures, which is accentuated in the initial years of the drought and stabilized in the final years. There is a decrease in expenditures related to the areas of public administration, legislative, culture, sport/leisure and education. These results indicate a strategic response from local public managers throughout the drought, leading to budget adjustment measures in the most affected municipalities. We also document that municipalities with a higher poverty rate are significantly more affected by drought in terms of reduced current expenditure than municipalities with a lower poverty rate, suggesting that extreme weather events can contribute to socioeconomic inequality, highlighting environmental justice considerations in understanding who bears the costs of natural disasters.